Autophagic control of cardiac steatosis through FGF21 in obesity-associated cardiomyopathy. (1st June 2018) - Rupérez, C.; Lerin, C.; Ferrer-Curriu, G.; Cairo, M.; Mas-Stachurska, A.; Sitges, M.; Villarroya, J.; Giralt, M.; Villarroya, F.; Planavila, A.
Abstract: Objective: High-fat diet-induced obesity leads to the development of hypertrophy and heart failure through poorly understood molecular mechanisms. We have recently shown that fibroblast growth factor-21 (FGF21) is produced by the heart and exerts protective effects that prevent cardiac hypertrophy development and oxidative stress. The aim of this study was to determine the effects of FGF21 on the cardiomyopathy associated with obesity development. Results: Fgf21 −/− mice showed an enhanced increase in the heart weight/tibia length (HW/TL) ratio in response to the high-fat diet. In keeping with this, echocardiographic measurements confirmed enhanced cardiac hypertrophy in Fgf21 −/− mice. At the cellular level, the area of cardiomyocytes was increased in Fgf21 −/− mice fed a high-fat diet. Furthermore, a high-fat diet induced fatty acid oxidation in the hearts of Fgf21 −/− mice accompanied by an increase in cardiac oxidative stress. Oil-red O staining revealed the presence of higher amounts of lipid droplets in the hearts of Fgf21 −/− mice fed a high-fat diet relative to wt mice fed this same diet. Finally, Fgf21 −/− mice fed a high-fat diet showed impaired cardiac autophagy and signs of inactive cardiac lipophagy, suggesting that FGF21 promotes autophagy in cardiomyocytes. Conclusions: Our data indicate that a lack of FGF21 enhances the susceptibility of mice to the development of obesity-related cardiomyopathy. Furthermore, we demonstrate that this cardiac dysfunction is associated with deleterious lipid accumulation in the heart. An impaired ability of FGF21 to promote autophagy/lipophagy may contribute to lipid accumulation and cardiac derangements. Highlights: Lack of FGF21 enhances the cardiac hypertrophy associated with obesity development. FGF21 insufficiency leads to cardiac fat accumulation during obesity. FGF21 controls autophagic pathways in the heart. Impaired lipophagy may lead to cardiac lipotoxic adiposity in Fgf21-null mice.